Integrated Organic Geochemical Characterization of Deltaic Source Rock in The Kutai Kartanegara Area, East Kalimantan - Jamaluddin; Desianto Payung Battu (Lembaran publikasi minyak dan gas bumi, 2026)
The Kutai Kartanegara area, East Kalimantan, is part of the Mahakam deltaic system, which is recognized as one of Indonesia’s major hydrocarbon-producing regions. This study aims to characterize deltaic source rocks and evaluate their hydrocarbon potential using an integrated organic geochemical approach. Geochemical analyses of twelve Miocene shale samples reveal Total Organic Carbon (TOC) values ranging from 1.3 to 5.32 wt.%, with an average of 2.37 wt.%, indicating good to very good organic matter richness. Hydrogen Index (HI) and Tmax data indicate that the organic matter is predominantly Type III kerogen, with minor contributions from Type II/III kerogen, mainly derived from higher terrestrial plants. Tmax values ranging from 425 to 447°C and vitrinite reflectance values of 0.64–0.77% suggest thermal maturity levels from immature to early mature stages. Pr/n-C17 and Ph/n-C18 ratios indicate deposition under fluctuating oxic to anoxic conditions within deltaic to shallow-marine environments under a humid equatorial climate. Statistical and cluster analyses reveal source rock heterogeneity controlled by facies variations and thermal maturity. These results indicate that Miocene shales in the Kutai Kartanegara Area have high potential as gas-prone and mixed hydrocarbon source rocks and play a significant role in the petroleum system of the Mahakam Delta region.